The epithelial sodium channel and the cell migration - Marino, Gabriela I. (2013)
Sodium is the main extracellular cation, and its osmotic pressure is an important determinant of the extracellular fluid volume. We were interested in the expression and functional characteristics of the epithelial sodium channel (ENaC) that mediates the Na+ entry into the cells from the luminal fluid in many reabsorbing epithelia and in the human placenta. Aldosterone is a key regulator of ENaC channel and stimulates protein methylation on the β-subunit of ENaC. Aldosterone and 8Br-cAMP promoted cellular migration in a wound healing model in trophoblastic BeWo cells. Amiloride blocked this effect. Electrophysiological studies showed an increase in ENaC current in the presence of aldosterone. We suggest that aldosterone positively influences wound healing through methylation of ENaC. On the other hand, we found a diminished expression of the three subunits of the ENaC in the membranes of preeclamptic placentas in comparison with the normal ones and this may have consequences for the cell migration and ion transport involved in the pathophysiology of preeclampsia.